Carbon dioxide embolism during transanal total mesorectal excision: A hint of prevention from a case report. Issue 3 (13th March 2022) - Fujii, Masakazu; Kato, Kentaro; Ichimaru, Chisato; Kushiya, Hiroki; Umemoto, Kazufumi; Furukawa, Shotaro; Okada, Naoya; Imamura, Kiyotaka; Yamabuki, Takumi; Kinoshita, Yoshihiro; Takada, Minoru; Ambo, Yoshiyasu; et al.
Abstract: Transanal total mesorectal excision is a relatively new approach for treating lower rectal cancer. Carbon dioxide embolism is a critical complication of this procedure. We report the case of a 69‐year‐old man with lower rectal cancer who underwent transanal total mesorectal excision followed by laparoscopic low anterior resection. He had a sudden intraoperative carbon dioxide embolism during the transanal mesorectal excision. During the ventral dissection of the rectum, end‐tidal carbon dioxide and blood oxygen saturation suddenly decreased. We stopped the insufflation of carbon dioxide and suspended the procedure. There was no circulatory collapse, and the vital signs gradually recovered; therefore, we resumed the surgery approximately 30 minutes later and completed it without additional complications. Upon reviewing the video, we found a small injured vein that would aspirate carbon dioxide. These findings suggested that careful hemostasis is essential to prevent carbon dioxide embolus during transanal total mesorectal excision.